Multilocus PCR-RFLP profiling in Trypanosoma cruzi I highlights an intraspecific genetic variation pattern (2012)
Chagas disease represents a serious problem in public health. This zoonotic pathology is caused by the kinetoplastid Trypanosoma cruzi which displays a high genetic diversity falling into six Discrete Typing Units (TcI–TcVI). In Colombia, the prevalent DTU is TcI with findings of TcII, TcIII and TcIV in low proportions. The aim of this work was to observe the genetic variability within TcI using a multilocus PCR-RFLP strategy. We analyzed 70 single-celled clones from triatomines, reservoirs and humans that were amplified and restricted via ten PCR-RFLPs targets across TcI genome, the restriction fragments were used to construct phylograms according to calculated genetic distances. We obtained five polymorphic targets (1f8, HSP60, HSP70, SAPA and H1) and the consensus tree constructed according to these regions allowed us to observe two well-defined groups with close association to the transmission cycles (domestic/peridomestic and sylvatic) of Chagas disease in Colombia. Our findings allowed us to corroborate the previous reported genotypes based on the intergenic region of mini-exon gene. More studies examining the genetic diversity among T. cruzi I populations must be conducted in order to obtain a better understanding in regions where this DTU is endemic.